Rhythm dances in Bela Bartok : An analysis of Mirkokosmos No. 2 and No. 6, Volume 6 for piano / Nurul Nadiah Jamaluddin - Jamaluddin, Nurul Nadiah (Faculty of Music, 2014)
The excerpt was taken from the Cambridge Companion to Bartok book. Bartok's contribution in most of his works was widely known for compositions that were strongly influenced by his folk music studies. Bailey (200 I) wrote that "a major contribution to the shaping of Bartok's artistic aesthetic was his folk-music research."(p.1). He was also known as a concert pianist, music editor and teacher. Ujji-Hilliard (2004) noted that "during the 1930's, the 50-year-old Bartok was already a well known and successful composer, pianist, and most of all, a world renowned ethnomusicologist." (p.1) Sadie and Grove (1980) noted that "the greatest composer of his country, he was responsible, with his friend Kodaly, for the awakening of serious interest in Hungarian folk music. His scientific research was thorough and extensive, and his music became deeply imbued with peasant culture, particularly Hungarian and Romanian. But he also engaged himself no less profoundly with the Western art music tradition.